FEM Analysis of Stress Charecteristics of Cut-off Wall in Rushan River Groundwater Reservoir. (November 2019) - Yu, Hairui; Yu, Songwei; Li, Chen; Li, Wanglin
Abstract: In order to evaluate the safety of stress intensity of the plastic concrete cut-off wall in Rushan River underground reservoir, the most dangerous section of the cut-off wall was selected, the stress distribution characteristics of the cut-off wall were analyzed by ABAQUS finite element analysis method, the safety strength was rechecked, and the calculation results are compared with the stress calculation results of the elastic foundation beam method. The following conclusions are drawn. The calculation results of the two methods show that the water level difference between the two sides of the cut-off wall has a great influence on the stress of the cut-off wall. The maximum compressive stress of cut-off wall is less than 3 Mpa and the maximum tensile stress is less than 0.65 Mpa, which meets the design strength of plastic concrete cut-off wall. ABAQUS finite element analysis method is feasible in the stress analysis of cut-off wall. Compared with the results of elastic foundation beam method, the finite element method can better reflect the stress distribution and displacement deformation on both sides of cut-off wall. ABAQUS finite element analysis method has certain advantages in stress analysis of cut-off wall.